AB0943 Short-term ultrasound multi-target monitoring of anti-TNF alpha treatment in patients with psoriatic arthritis. (23rd January 2014) - Gutierrez, M.; Di Geso, L.; Salaffi, F.; De Angelis, R.; Bertolazzi, C.; Tardella, M.; Filosa, G.; Filippucci, E.; Grassi, W.
Abstract : Background: There is an increasing evidence supporting power Doppler (PD) ultrasound as a sensitive imaging technique for the assessment of disease activity and therapy monitoring in patients with chronic arthritis, including psoriatic arthritis (PsA). The recent availability of probes with Doppler frequency higher than 10 MHz allows the detection of even minimal blood flow changes of superficial targets such as nail and skin (1). Objectives: To investigate the role of PD ultrasound for the assessment of blood flow changes induced by anti-TNFα therapy at five target areas (joint, tendon, enthesis, skin and nail) in patients with PsA. Methods: Sixteenpatients with diagnosis of PsA (receiving different anti-TNFα: 9 adalimumab, 4 etanercept and 3 infliximab), and clinical involvement of multiple targets (joint, tendon, enthesis, skin, nail) were enrolled. Before the PD ultrasound assessment all patients underwent a clinicalexamination aimed to detect tenderness and/or swellingat joints, tendons, and entheses level. Moreover, HAQ modified for spondyloarthritis (-S), PASI and NAPSI were assessed. At baseline, all clinically involved targets were scannedand those showing the highest expression of PD signal, one for each target area, were selected to be scanned at follow-up visit 8 weeks after. For each target a semi-quantitative PD scoring (0 to 3) was used. Clinical and PD assessments were performed on the same day both at baseline and at follow-up visit. Results: A total of 60 targets (16 joints, 9 tendons, 11 enthesis, 16 psoriatic plaques and 8 psoriatic nails) were assessed. A significant improvement of the clinical scores was found at follow-up with respect to the baseline: HAQ-S [mean ± SD: 0.88±0.20 vs 0.47±0.12 respectively (p=0.0001)]; PASI [mean ± SD: 17.5±5.3 vs 8.0±2.7 respectively (p=0.0001)] and NAPSI [mean ± SD: 2.2±2.6 vs 0.8±1.0 respectively (p=0.35)]. PD ultrasound findings at baseline and follow-up were: joint [median; range: 2.5; 1-3 vs 1; 0-2, respectively (p=0.0001)], tendon [median; range: 2; 0-3 vs 0; 0-1, respectively (p=0.04)]; enthesis [median; range: 1.5; 0-2 vs 0 0-2, respectively (p=0.04)], skin [median; range: 3; 2-3 vs 0.5; 0-2, respectively (p=0.0001)] and nail [median: range: 0; 0-1 vs 0; 0-1, respectively (p=0.3657)]. There was no significant correlation between HAQ-S and PD ultrasound findings (p=0.51)at baseline and at follow-up (p=0.93), respectively.The mean time (± SD) spent on baseline ultrasound examinations was: 10.5 (± 2.0) minutes and no more than 7 (± 1.5) minutes for follow-up assessment. Conclusions: PD ultrasound provides a useful and feasible method for short-term multi-target monitoring of anti-TNFα therapy effect in patients with PsA. Ongoing investigation including a wider cohort of patients, more centres and testing the reproducibility will provide further information regarding the advantages and limitations of this multi-target approach in patients with PsA. References: Gutierrez M, De Angelis R, Bernardini ML, et al. Clinical, power Doppler sonography and histological assessment of the psoriatic plaque: short-term monitoring in patients treated with etanercept. Br J Dermatol 2011;164:33-37. Disclosure of Interest: None Declared